Using Opinion Proof Strategy to Improve Reading Ability of Second Semester Students of IKIP PGRI Madiun - Rahmasari, Brigitta Septarini (Universitas Pendidikan Mandalika (UNDIKMA), 2016)
Opinion Proof is a learning strategy that is used to overcome the problem of reading in English. Opinion Proof strategy can be used to help facilitate students' reading comprehension in English. The objective of the research is to determine whether or not Opinion Proof Strategy can improve reading ability of second semester of IKIP PGRI Madiun. This research is a classroom action research. There are several steps in each cycle. They are planning, action, observation and reflection. The techniques of collecting the data are test, observation, interview, and documentation. Meanwhile, the thecniques of analyzing the data are descriptive statistics, reducing, displaying and conclsion. With Proof Opinion strategy, students are more creative, students can develop the imagination, the students easily understand the content of the reading of the text, motivate the students to read, and students do not feel bored.